Evaluation of inhibitor activity of bacterial sialidase from Clostridium perfringens against Newcastle disease virus in the cell culture model using chicken embryo fibroblast - Kurnia, Ryan Septa; Setiawaty, Rahajeng; Natih, Ketut Karuni Nyanakumari; Nugroho, Christian Marco Hadi; Silaen, Otto Sahat Martua; Widyaningtyas, Silvia Tri; Tarigan, Simson; Ibrahim, Fera; Sudarmono, Pratiwi Pudjilestari (Journal of Advanced Veterinary and Animal Research, 2022)
Objective: The Newcastle disease virus (NDV) is an infectious disease that causes very high economic losses due to decreased livestock production and poultry deaths. The vaccine’s ineffectiveness due to mutation of the genetic structure of the virus impacts obstacles in controlling the disease, especially in some endemic areas. This study aimed to provide an alternative treatment for NDV infection by observing the viral replication inhibitor activity of Clostridium perfringens sialidase in primary chicken embryo fibroblast (CEF) cells. Materials and Methods: The virus was adapted in CEF monolayer cells, then collected thrice using the freeze–thaw method and stored at −20°C for the next step in the challenge procedure. C. perfringens crude sialidase was obtained, but it was further purified via stepwise elution in ion exchange using Q Sepharose® Fast Flow and affinity chromatography with oxamic acid agarose. The purified sialidase was tested for its toxicity, ability to breakdown sialic acid, stopping viral replication, and how treated cells expressed their genes. Results: According to this study, purified C. perfringens sialidase at dosages of 187.5, 93.75, and 46.87 mU effectively hydrolyzes CEF cells’ sialic acid and significantly inhibits viral replication on the treated cells. However, sialidase dosages of 375 and 750 mU affected the viability of monolayer CEF cells. Interestingly, downregulation of toll-like receptor (TLR)3 and TLR7 (p < 0.05) in the sialidase-treated group indicates viral endocytosis failure. Conclusions: By stopping endocytosis and viral replication in host cells, sialidase from C. perfringens can be used as an alternative preventive treatment for NDV infection. J. Adv. Vet. Anim. Res., 9(2): 335–345, June 2022 http://doi.org/10.5455/javar.2022.i600